Evaluation of comprehensive care for older adults in primary care services - Placideli, Nadia [UNESP]; Lodeiro Castanheira, Elen Rose [UNESP]; Dias, Adriano [UNESP]; Silva, Pedro Alcantara da; Fernandes Carrapato, Josiane Lozigia [UNESP]; Sanine, Patricia Rodrigues [UNESP]; Machado, Dinair Ferreira [UNESP]; Mendonca, Carolina Siqueira [UNESP]; Tortorelli Zaril, Thais Fernanda [UNESP]; Nunes, Luceime Olivia [UNESP]; Casquel Monti, Jose Fernando [UNESP]; Araujo Hartz, Zulmira Maria de; et al. (Revista De Saude Publica, 2020)
OBJECTIVE: To evaluate the performance of comprehensive care for older adults in primary care services in the Brazilian Unified Health System in the state of Sao Paulo, Brazil. METHODS: A total of 157 primary care services from five health regions in midwestern Sao Paulo responded, from October to December 2014, the pre-validated 2014 questionnaire for primary care services assessment and monitoring. We selected 155 questions, based on national policies and guidelines on this theme. The responses indicate the service performance in older adults' care, clustered into three areas of analysis: health care for active and healthy aging (45 indicators, d1), chronic noncommunicable diseases care (89 indicators, d2), and support network in aging care (21 indicators, d3). Performance was measured by the sum of positive (value 1) or negative (value 0) responses for each indicator. Services were clustered according to k-means of the performance scores of each domain. After weighting the domains (Z tests), we estimated the associations between the scores of each domain and independent management variables (typology, planning and evaluation of services), with simple and multiple linear regression. RESULTS: Chronic noncommunicable diseases care (d2) showed, for all clusters, better average performance (55.7) than domains dl (35.4) and d3 (39.2). Service performance in the general area of planning and evaluation associates with the performance of older adults' care. CONCLUSIONS: The evaluated services had incipient implementation of comprehensive care for older adults. The evaluation framework can contribute to processes to improve the quality of primary health care.
Keywords: Health Services for Older Adults; Comprehensive Health Care; Primary Health Care; Health Services Research; Brazilian Unified Health System